Intelligent Detection of Towers and Lines in Passageways Using Hybrid Evolutionary Computational Intelligence (HECI) Algorithms - Li, Ning; Liang, Helei; Guo, Lianju; Wang, Xiaoying; Zhang, Jian (Informatica, 2025)
Identification of towers and lines in passageways is important in infrastructure surveillance, assessment, and the formation of automated surveillance systems. Indeed, conventional AI-based solutions for identification tasks are not immune to certain types of indeterminacy that arise in complicated contexts and can, therefore, yield unpredictable results. This paper presents a new method that integrates AI detection methods with the Hybrid Evolutionary Computational Intelligence (HECI) model to solve these uncertainties and increase decision-making efficacy. The computational framework is built using inspection data from real infrastructure evaluations and simulated scenes with different lighting and hidden objects. This is a reasonable basis for further improving detection performance using the proposed methodology, which uses AI models in partnership with the HECI algorithm to assess the detection results. Compared to conventional detection methods, the HECI-enhanced approach outperforms traditional models by more than 25%, achieving a remarkable detection accuracy of 99.47%. In environments where traditional AI methods may struggle, this approach enhances precision by approximately 15%. The model’s versatility makes it well-suited for applications associated with infrastructure inspection, where precision and robustness are crucial. Integrating HECI helps maintain the AI-based detection system’s adaptability to unpredictable environmental changes, enhancing the effectiveness of safety detection and automated inspection systems. This approach significantly enhances the identification of towers and lines in passages, especially camera angles and obstructions in complicated environments, showing the promise of HECI as the next-generation tool for infrastructure monitoring.